2003
DOI: 10.1007/s005950300003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Absorbable Clips Compared with Metal Clips for Cystic Duct Ligation in Laparoscopic Cholecystectomy

Abstract: The results of this study suggest that absorbable clips are as safe and effective as standard metal clips for vessel and duct ligation in LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…However, in our opinion, double clipping of the appendicular stump is not necessary. This has been shown by the use of single clips closing the cystic duct in laparoscopic cholecystectomies [14,15]. In addition, the safety of a single loop has been shown to be sufficient by Beldi et al [16], as well as by our group [6].…”
Section: Discussionmentioning
confidence: 86%
“…However, in our opinion, double clipping of the appendicular stump is not necessary. This has been shown by the use of single clips closing the cystic duct in laparoscopic cholecystectomies [14,15]. In addition, the safety of a single loop has been shown to be sufficient by Beldi et al [16], as well as by our group [6].…”
Section: Discussionmentioning
confidence: 86%
“…Clips migrated at regular intervals from their initial site to either the peritoneal cavity or the common bile duct, serving as a potential nidus for gallstone formation. Yano et al [18] showed in their retrospective study that the mean operative time in the absorbable group was significantly shorter, and that the morbidity with the use of metal clips was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Several variants of LC have been described, but evidence about their effectiveness is scarce (Low quality evidence). On the other hand, there is no evidence of major complications with outpatient LC (Low quality evidence) (Al-Ghnaniem, 2003;Koc, 2003;Harling, 2000;SIGN, 2004;Ladocsi, 1997;Millat, 1997;Thornton, 2002;Kitano, 1993;Barczynski, 2004;Nande, 2002;Trichak, 2003;Novitsky, 2005;Lai, 2003;Zhou, 2006;Corbitt, 1991;Bordelon, 1993;Lane GE, 1993;Janssen, 2003;Cengiz, 2005;Edelman, 1995;Shekarriz, 2003;Bencini, 2003;Yano, 2003;Verma, 2006;Grace, 1991;Martinez Vieira, 2004;Lau, 2002;Pattillo, 2004;Bueno Lledo, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In two low-quality RCT assistance with a water irrigation system and a hydrodissection with adrenaline-lidocaine-saline solution, as an alternative to dissection, showed clinically modest results (Shekarriz, 2003) and no differences respect to traditional dissection system (Caliskan, 2006). The use of various types of ligature and suture as an alternative to conventional stapling is supported by a retrospective cohort81 and two retrospective case series (Yano, 2003;Yeh, 2004). Finally, the use of 0.5% bupivacaine-soaked Surgicel in the gallbladder proved in a cohort study, appear to be effective for control visceral pain after laparoscopic cholecystectomy, but port-site infiltration alone would be ineffective (Verma, 2006)…”
Section: Technological Variantsmentioning
confidence: 92%